Improving the system of technical diagnostics and environmentally safe operation of soil hydraulic structures on small rivers - Hapich, H. V.; Pikarenia, D. S.; Orlinska, O. V.; Kovalenko, V. V.; Rudakov, L. M.; Chushkina, I. V.; Maksymova, N. M.; Makarova, T. K.; Katsevych, V. V.; Пікареня, Д. С.; Максимова, Н. М. (ПП "ТЕХНОЛОГІЧНИЙ ЦЕНТР", 2022)
This paper reports the results of studying soil hydraulic structures (SHS) of the CC1 class of conse-quences on small rivers. The repre-sentativeness of the results for the domestic and world practice of fur-ther operation of such structures is ensured by the typical technical and technological approaches to the con-struction, materials, and conditions of their work. Dams are built of soil materials and operated over signif-icant time periods while their stan-dard service life has been exhausted, which increases the environmental and technical danger of their fur-ther operation. Visual surveys were conducted and the technical condi-tion was instrumentally diagnosed by the geophysical method of the earth's natural pulsed electromagnetic field (ENPEMF); observational data were mathematically treated. The possi-bility of arranging areas of increased water filtration through the SHS body was substantiated, as well as watering, loosening, and suffusion; potentially dangerous zones prone to landslides, cracks, and collapse were determined. The probability of risk of an accident on dams was esti-mated at their cascading arrange-ment as a result of filtration deforma-tions of the body and the base of the structure. Under current operating conditions, the possibility of letting the normative and excess (forced) water volumes through water dis-charge facilities due to precipitation or a breakthrough of the structure located upstream was estimated. The proposed approach makes it possible to manage the cascade of hydrau-lic structures at different stages of operation: planned, operational decision-making, forecasting. This allows diagnostic examinations to be performed in order to identify struc-tures that require priority in raising funds for repair and restoration work or demolition (dismantling).
Keywords: hydraulic structure; soil dam; small river; geophysical research methods; filtration deformations